Does fertilizing corn with poultry litter enrich the grain with mineral nutrients? - Tewolde, H.; Sistani, K.R.; Feng, G.; Menkir, A. (Wiley, 2019)
Whether poultry litter (PL) increases concentration of selected mineral elements in corn (Zea mays L.) grain has not been well investigated. The objective of this study was to determine whether fertilizing corn with PL enriches the grain and other plant parts with selected mineral elements. Corn was grown in the field in northern Mississippi with no fertilization (UTC) or fertilization with 9 or 18 Mg ha–1 PL, or 202 kg ha–1 NH4NO3–N applied in the fall vs. spring. Poultry litter, regardless of application timing, increased soil total N and extractable P, K, Mg, Cu, Mn, and Zn by up to twofold relative to NH4NO3–N. Litter also increased concentration of N, P, Cu, and Zn in leaves and stems but did not particularly enrich the grain with any of the measured elements. Grain N, P, K, Mg, Fe, Mn, and Zn concentrations were highest in corn fertilized with 202 kg ha–1 NH4NO3–N applied in the spring. Poultry litter increased grain concentrations of these elements to equal those of the NH4NO3–N fertilized corn only if it also increased the N level in the plant and the grain. High positive correlation of grain N with grain P, K, Mg, Fe, Zn, and Mn suggests that conditions that increase grain protein level would also increase the levels of P, K, Mg, Fe, Zn, and Mn in the grain and that the level of mineral elements in corn grain is dependent on the level of N nutrition of the corn plant.